IMPLEMENTASI METODE PROBLEM BASED LEARNING BERBASIS AUDIOVISUAL DALAM PEMBELAJARAN MENULIS TEKS EKSPLANASI - Ulfa Fitriah; Wiwin Winarti; Sary Sukawati (IKIP Siliwangi, 2019)
The background this research, seen from the ability of students who are less proficient in pouring ideas or ideas into eriting and the application of classroom learning methods is not aptimal so that student are less active in learning in class. The purpose of this study is to describe the implementation of autovisual based problem based learning methods.The method of this research is experimental method whit nonequivalent control group design. Samples taken are students of class VIII Mts which amounted to 20 students. Collection techniques used are wiewed from student observation sheets and test. Results from the analysis conducted in class VIII obtained an average of 75.7 and 82.6 on the final test, from the results of these studies proved that the increase.